Saving Epic Poetry: Literary Theory as a Political Tool in the Enlightenment - García-Minguillán, Claudia (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This article pretends to analyze how epic’s theory contributes to the formulation and legitimation of political roles of a society. From the Enlightenment’s beginnings, there was the fear that epic poetry’s disappearance was imminent/disappeared imminently. Faced with losing the ideological literature, there was both consequences: Toughen with literary rules or adapt the epic poetry to the social development. This variation of the classic paradigm favoured a passage from a warlike model to a pacific role, where the hero is not the soldier but the diplomatic, the politician, and even the philosopher. This trade, induced by the literary theory, lengthen epic genre’s life until the commence of XIX century.
Keywords: Epic; Literary Theory; Theory of Genres; Enlightenment; Politics